(untitled) (Bangladesh Veterinarian, 2011)
The rotifer Brachionus plicatilis was cultured with powdered dried Chlorella in treatment 1, live or fresh cultured Chlorella in treatment 2, and baker’s yeast in treatment 3. All the jars under three treatments were stocked with B. plicatilis at the initial density of 10 individuals per ml. The water temperature, air temperature, pH and dissolved oxygen were within the suitable range for B. plicatilis culture. The highest population densities of B. plicatilis in treatments 1, 2 and 3 were 60000, 50000 and 30000 (individual/L), respectively. The powered dried Chlorella was comparable with live Chlorella and may be used successfully as a feed for B. plicatilis. DOI: 10.3329/bvet.v27i2.7559 Bangl. vet. 2010. Vol. 27, No. 2, 91-98